PENEGAKAN HUKUM TERHADAP BANGUNAN DI BANTARAN SUNGAI KAHAYAN KELURAHAN PAHANDUT SEBERANG KOTA PALANGKA RAY - Rico Septian Noor (MORALITY: Jurnal Ilmu Hukum, 2019)
Problems regarding law and law enforcement are never finished to be discussed and discussed, including law enforcement related to spatial planning. Quite a lot of research and studies that examine law enforcement, especially in spatial planning on river banks. Likewise, the formulation of rules and policies made to change the spatial planning on the riverbanks can be properly enforced. Law enforcement efforts are of course also related to many factors. for example, the structure, substance, and culture of law which all lead to an imbalance between (Das sollen) or what has been expected by the people with (Das Sein) namely the reality in the implementation of law in society, by therefore, there is a need for a solutive effort given by the local government, in this case, the focus of the study is on law enforcement on buildings on the Kahayan Riverbanks.